(untitled) (CIPEEX, 2025)
This summary was based on the differentiation between natural and artificial immunity in humans. The immune response can be divided into innate and adaptive. Innate immunity is the first line of defense against aggressors and involves molecular and cellular processes that can trigger a rapid and effective inflammatory response, being composed of physical barriers, such as the skin, and internal actions, such as the acidic pH of gastric juice, which destroys pathogens. In addition, if innate immunity cannot resolve the aggression, there is also adaptive immunity, which consists of the participation of B and T lymphocytes, through humoral and cellular acquired immunity, respectively. Adaptive immunity is slower, progressive, very specific, and has immunological memory. For body homeostasis, the ideal is for the body to act on both innate and adaptive immunity, with adaptive immunity being the target of drugs and immune therapies. Thus, vaccination is an important way to stimulate the immune response, because from the inoculation of antigens, B lymphocytes are stimulated to produce antibodies. In this case, contact with the pathogen was intentionally provoked in order to generate immunological memory and quickly overcome the infection in a new exposure. Thus, it says that there was an artificial immunization, and therefore, the importance of vaccination is recognized worldwide. On the other hand, if the person has a primary infection, that is, comes into direct contact with a virus, bacteria, fungus, or parasite from contact with fomites or other forms of transmission, the body will generate immunity naturally. Thus, we have an example of natural immunity, since the person was naturally stimulated to produce a response against the aggressor agent.